The business model for access to affordable re on economic, social, and environmental value : A review - Erdiwansyah, E.; Gani, Asri; Rizalman, Mamat; Nizar, Muhammad; Yana, Syaifuddin; S. M., Rosdi; Mohd Zaki, Muhammad Faiz; Sardjono, Ratnaningsih Eko (AGH University of Science and Technology Press, 2023)
Renewable energy has the potential to power the global economy and effective business models will significantly aid this goal, being among the most critical factors in spurring expansion in the energy industry. This paper reviews articles that discuss business models in the renewable energy sector. Long-term economic, social, and ecological stability is concerned. Previous studies have neglected the environmental sustainability of renewable energy business models, focusing on their technical, social, and economic aspects, primarily for energy access. The business models for solar home and pico systems relied heavily on lowering costs through creative payment plans for customers to be commercially viable. The demand for mini-grids requires end users to launch businesses that can leverage electrification initiatives to be commercially via-ble. The success of a mini-grid depends on the average consumption and reve-nue per user. Affordability, unmet energy needs, low electricity demand, lack of financing, unfamiliar business models, and immature markets have imped-ed energy access in Indonesia. Our analysis revealed that future studies in this field must include environmental sustainability to provide a complete picture for decision-makers. Renewable energy needs in Indonesia can be achieved through the sustainability domain, policy makers can consult this evidence set.